2016
DOI: 10.1002/ange.201605129
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne Metathesis with Silica‐Supported and Molecular Catalysts at Parts‐per‐Million Loadings

Abstract: Improvement of the activity, stability, and chemoselectivity of alkyne‐metathesis catalysts is necessary before this promising methodology can become a routine method to construct C≡C triple bonds. Herein, we show that grafting of the known molecular catalyst [MesC≡Mo(OtBuF6)3] (1, Mes=2,4,6‐trimethylphenyl, OtBuF6=hexafluoro‐tert‐butoxy) onto partially dehydroxylated silica gave a well‐defined silica‐supported active alkyne‐metathesis catalyst [(≡SiO)Mo(≡CMes)(OtBuF6)2] (1/SiO2‐700). Both 1 and 1/SiO2‐700 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…In terms of catalytic performance, the cationic molybdenum alkylidyne NHC complexes are at least comparable to the catalysts recently published by Fürstner et al, which showed exceptional tolerance against functional groups and to some degree against water at high catalyst loadings (>1 mol %), , as well as to the catalysts reported by Tamm et al, which reached TONs > 180 000, though only for carefully and highly purified S1 , , in that the catalysts presented here allow for high TONs for various substrates without extensive purification. Furthermore, the turnover frequencies after 5 min (TOF 5min ) were determined for the conversion of S1 – S6 with Mo6 at a catalyst loading of 0.005% and a concentration of 660 mM (Table ).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In terms of catalytic performance, the cationic molybdenum alkylidyne NHC complexes are at least comparable to the catalysts recently published by Fürstner et al, which showed exceptional tolerance against functional groups and to some degree against water at high catalyst loadings (>1 mol %), , as well as to the catalysts reported by Tamm et al, which reached TONs > 180 000, though only for carefully and highly purified S1 , , in that the catalysts presented here allow for high TONs for various substrates without extensive purification. Furthermore, the turnover frequencies after 5 min (TOF 5min ) were determined for the conversion of S1 – S6 with Mo6 at a catalyst loading of 0.005% and a concentration of 660 mM (Table ).…”
supporting
confidence: 86%
“…Starting from “ill-defined” metathesis catalysts, the number of well-defined homogeneous alkyne metathesis catalysts has grown unceasingly to the point that structure and reactivity can be precisely controlled . The groups of Schrock, Fürstner, Tamm, Veige, Zhang, Moore, Fischer, and Cummins developed current state-of-the-art catalysts bearing silanolates, amides, fluorinated alkoxides, iminato or multidentate ligands. A common feature is the tetracoordinate nature of the active catalyst systems.…”
mentioning
confidence: 99%
“…The homogeneous catalyst MoF6 and its immobilized form MoF6@SiO2 showed unprecedented catalytic activity at parts-per-million loadings; however, lower activity was observed for the heterogeneous system, presumably owing to the rigidity of the surface species. 62 Noteworthy, the molecular catalysts MoF6 and MoSiF6 showed comparable activity in the selfmetathesis of 1-phenyl-1-propyne, revealing that the replacement of one fluroalkoxide by the (tBuO)3SiO group does not lead to a deterioration in the catalytic activity. 63 The X-ray crystal structure of MoSiF6 showed that the siloxide is bound in a chelating  2 O,O' fashion in the solid state.…”
Section: Introductionmentioning
confidence: 93%
“…54−61 Among the most active catalysts are also the 2,4,6-trimethylbenzylidyne complexes MoF6 (Figure 1, M = Mo, n = 2) and WF3 (M = W, n = 1), which even perform terminal alkyne metathesis efficiently. [11][12][13]62,63 Additionally, MoF6 and related complexes have been applied in ring-opening alkyne metathesis polymerization (ROAMP) 64−67 neous catalysts by immobilization onto dehydroxylated silica. 12,14,68 The proposed mechanism of alkyne metathesis first suggested by Katz proceeds via metallacyclobutadiene (MCBD) intermediates, which form by [2+2] cycloaddition of the metal alkylidyne and an alkyne.…”
Section: ■ Introductionmentioning
confidence: 99%